1977
DOI: 10.1002/bms.1200040212
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of enantiomeric compounds. I—simultaneous measurement of the optical isomers of amphetamine in human plasma and saliva using chemical ionization mass spectrometry

Abstract: A sensitive and specific method for the quantitative determination of the optical isomers of amphetamine from human plasma and saliva is described. Amphetamine was extracted from basified plasma or saliva with hexane and then derivatized by reaction with N-pentafluorobenzoyl-S-(-)-prolyl-1-imidazolide. The reaction of the amphetamine enantiomers with this chiral reagent yields diasteriomers which are easily resolved by gas liquid chromatography. The resolved diasteriomers upon elution from the gas chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The choice of IS often plays an important role in obtaining an accurate measurement by this technique. The use of stable-isotopically labeled IS has given good results [9][10][11]. Such stable isotopes, however, are not readily available due to their high price and complicated syntheses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The choice of IS often plays an important role in obtaining an accurate measurement by this technique. The use of stable-isotopically labeled IS has given good results [9][10][11]. Such stable isotopes, however, are not readily available due to their high price and complicated syntheses.…”
Section: Discussionmentioning
confidence: 98%
“…1) prepared in this study was shown to be a desirable IS on account of its distinct separation from unlabeled MA and since it permits the use of EI as well as CI mass spectrometry. PDM can be synthesized at a lower expense and by a simpler procedure than by introducing deuterium In humans cases, the values are calculated after converting the weights into 60 kg into other positions of the amine, such as the 3-carbon of propyl group and the phenyl ring [2,11]. The cost was approximately one third of that of previous methods.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the various methylene dioxy amphetamines show only marfor the l-isomer is approximately 39% longer, indicating a slower metabolism than the d-form. Furthermore half-lives of both isomers are reduced to about 7 hours due to enhanced elimination via acidification of the urine (Matin et al 1977;Wan et al 1978). Amphetamine metabolism includes deamination, oxidation and hydroxylation.…”
Section: Amphetamine and Amphetamine-like Drugsmentioning
confidence: 99%
“…The relationship between the saliva/plasma drug concentration ratio, pKa, pH and binding is expressed by the equations of Rasmussen/Matin [45]. The pH value of saliva ranges from 5.8 to 7.6 while the pH value of blood remains fairly constant.…”
Section: Biological Data On Drug Monitoring In Salivamentioning
confidence: 99%